2004
DOI: 10.1161/01.cir.0000117402.70689.75
|View full text |Cite
|
Sign up to set email alerts
|

Slow Conduction and Enhanced Anisotropy Increase the Propensity for Ventricular Tachyarrhythmias in Adult Mice With Induced Deletion of Connexin43

Abstract: Background-Connexin 43 (Cx43) is a major determinant of conduction in the ventricular working myocardium of mammals. We investigated the effect of decreased Cx43 expression on conduction velocity and arrhythmogenesis using adult mice with inducible deletion of Cx43. Methods and Results-Cx43Cre-ER(T)/ϩ mice, in which 1 coding region of the Cx43 gene was replaced by Cre-ER(T), were mated to Cx43 fl/fl mice, generating Cx43 Cre-ER(T)/fl mice. Application of 4-hydroxytamoxifen (4-OHT) induced Cre-ER(T)-mediated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
261
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(281 citation statements)
references
References 31 publications
19
261
1
Order By: Relevance
“…38 However, some recent investigations have shown that the slowing of impulse propagation depends on more severe reductions in Cx43 abundance. 3,39 The fluidity of cholesterol-rich domains in plasma membrane is important to gap junctional coupling. 40 In our experimental animals, the membrane-enrichment by cholesterol will decrease the fluidity and impair the coupling.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, some recent investigations have shown that the slowing of impulse propagation depends on more severe reductions in Cx43 abundance. 3,39 The fluidity of cholesterol-rich domains in plasma membrane is important to gap junctional coupling. 40 In our experimental animals, the membrane-enrichment by cholesterol will decrease the fluidity and impair the coupling.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the intercellular electrical uncoupling of ventricular cardiomyocytes also represents a major role in arrhythmogenesis during chronic ischemic heart disease 3. The gap‐junctional protein connexin 43 (Cx43) coordinates with cardiomyocyte activation and allows intercellular communication,4 whereas its downregulation and nonuniformity increases the risk of ventricular arrhythmia directly 5. Inhibiting interleukin‐1β (IL‐1β) following MI increases the expression of Cx43, thereby representing a novel antiarrhythmic property 6.…”
Section: Introductionmentioning
confidence: 99%
“…It is well appreciated that altered expression and/or distribution of Cx43-containing gap junctions are common features of diseased myocardium (1)(2)(3). Recent studies have demonstrated that cardiac-specific loss of Cx43 is sufficient to slow myocardial conduction velocity and induce unidirectional block resulting in an arrhythmogenic substrate and sudden cardiac death (SCD) in mice (4,5). However, it is less well understood how gap junctions are regulated and maintained at the ICD.…”
Section: Introductionmentioning
confidence: 99%